2017
DOI: 10.1007/s10474-017-0729-z
|View full text |Cite
|
Sign up to set email alerts
|

Cubes and their centers

Abstract: Abstract. We study the relationship between the sizes of sets B, S in R n where B contains the k-skeleton of an axes-parallel cube around each point in S, generalizing the results of Keleti, Nagy, and Shmerkin [6] about such sets in the plane. We find sharp estimates for the possible packing and boxcounting dimensions for B and S. These estimates follow from related cardinality bounds for sets containing the discrete skeleta of cubes around a finite set of a given size. The Katona-Kruskal Theorem from hypergra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 10 publications
(18 reference statements)
0
29
0
Order By: Relevance
“…In particular, they proved that sets of fractional dimension can differentiate some L p spaces. A similar geometric problem, in which circles are replaced by k-skeletons of ncubes with axes-parallel sides was recently studied by T. Keleti, D. Nagy and the second author in [4], for the case n = 2, and by R. Thornton in [9] for n ≥ 3. In [4] it was shown that a set in the plane containing a 1-skeleton with center in every point of [0, 1] 2 can have Lebesgue measure 0, and it was investigated how small its fractal dimension can be for different notions of dimension.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, they proved that sets of fractional dimension can differentiate some L p spaces. A similar geometric problem, in which circles are replaced by k-skeletons of ncubes with axes-parallel sides was recently studied by T. Keleti, D. Nagy and the second author in [4], for the case n = 2, and by R. Thornton in [9] for n ≥ 3. In [4] it was shown that a set in the plane containing a 1-skeleton with center in every point of [0, 1] 2 can have Lebesgue measure 0, and it was investigated how small its fractal dimension can be for different notions of dimension.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
“…In [4] it was shown that a set in the plane containing a 1-skeleton with center in every point of [0, 1] 2 can have Lebesgue measure 0, and it was investigated how small its fractal dimension can be for different notions of dimension. The arguments from [4,9] are direct and do not involve any maximal operators. The goal of this paper is to study a natural k-skeleton maximal operator associated to this geometric problem.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Roughly speaking, the k-dimensional boundary of a cube with axes parallel sides in R n for 0 ≤ k < n. In R 3 , for example, the case k = 2 consists in considering the faces of the cube, k = 1 is for the set of edges of the cube and the case k = 0 describes the vertices. The problem of finding minimal values of the size for sets in R n containing k-skeletons centered at any point was recently studied by Keleti, Nagy and Shmerkin in [KNS18] and also by Thornton in [Tho17]. The main result in [KNS18] is that there exists a set containing a 1-skeleton centered at any point of the unit square [0, 1] 2 having Lebesgue measure zero and, moreover, with zero Hausdorff dimension.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In Section 5 we study the case when T is the k-skeleton (0 ≤ k < n) of a fixed axis parallel n-dimensional cube centered at the origin or the k-skeleton of a more general polytope. For the k-skeleton of axis parallel cubes Thornton [22] generalized the above mentioned two-dimensional results for packing and box dimensions (Theorem 5.2), found the estimate dim H B ≥ max(k, dim H S − 1) for Hausdorff dimension and posed the conjecture the this estimate is sharp. This conjecture was proved by Chang, Csörnyei, Héra and the author [3] not only for cubes but for more general polytopes (Theorem 5.6).…”
Section: Introductionmentioning
confidence: 89%
“…[11], [22]) If 0 ≤ k < n and B ⊂ R n contains a k-dimensional skeleton of an n-dimensional axis-parallel cube centered at every point S ⊂ R n of dimension s (for some dimension) then the best lower bound for the dimension (for the same dimension) of B is shown in the last column of the following table.…”
Section: Theorem 52 (Thornton [22])mentioning
confidence: 99%